Nutritional Quality and Starch Gelatinization Characteristics of Main Highland Barley Cultivars from Qinghai and Tibet - Qian WANG; Yanan TONG; Lili WANG; Bin DANG; Kunlun WU; Xijuan YANG; Fengzhong WANG; Liya LIU (Shipin gongye ke-ji)
Highland barley is a high-quality raw material for developing nutritious and healthy foods. In order to study the influence of various factors such as cultivars and origin on the nutritional quality and processing characteristics of highland barley, this paper collected 30 highland barley cultivars from Qinghai and Tibet, the primary producing areas of highland barley in China, to explore the variations in main nutritional composition and starch gelatinization characteristics. The results revealed significant variations in the nutritional composition of different highland barley samples. The contents of vital functional factors such as β-glucan, arabinoxylan (AX), and total phenols ranged from 3.74% to 6.54%, 5.63% to 11.51%, and 1.90 to 4.24 mg/g, respectively. Additionally, a highly significant negative correlation (P<0.01) was observed between the content of β-glucan and the total phenols. Furthermore, the cultivars also significantly influenced the starch gelatinization characteristics (P<0.05), with the peak viscosity of starch ranging from 468.67 to 4844.67 cP and the gelatinization temperature ranging from 66.30 to 86.85 ℃. The principal component analysis reduced the 15 indicators of nutritional components and pasting properties to 5 principal components, revealing that pasting properties, non-starch polysaccharides, AX, starch, and β-glucan played important roles in the quality evaluation of highland barley. Cluster analysis identified 12 highland barley varieties with high β-glucan (ranging from 5.62% to 6.54%), 11 with high AX (ranging from 10.37% to 11.51%), 1 with high total phenol (4.24 mg/g), and 10 with high pasting temperature (ranging from 81.05 to 86.85 ℃). Xining Chaiqing No.1 with the characteristics of high β-glucan, high AX, high gelatinization temperature, and moderate total phenolic content, may have advantages in the development of functional food with high activity and low glycemic index (GI).